CULTURAL LITERACY-BASED COACHING MODEL: ENHANCING QUALITY EARLY CHILDHOOD EDUCATION IN THE MERDEKA CURRICULUM FRAMEWORK - Liza, Muawanatul; Pramono, Pramono; Wahyuni, Sri (Jurnal Konseling Pendidikan Islam, 2025)
This study is based on the urgency of developing the quality of early childhood education through an approach relevant to the local cultural context in the independent curriculum. This study aims to analyze the application of a coaching model based on cultural literacy in improving the quality of early childhood education in the context of the Independent Curriculum. This study uses a qualitative case study approach, where researchers use interviews, observations, and documentation for data collection. The data analysis technique is carried out in a circular manner, from data display to data reduction and conclusion. The results of the study indicate that the coaching model based on cultural literacy in improving the quality of early childhood education in the context of the Independent Curriculum is carried out through teacher training in cultural literacy, development of local culture-based curriculum and teaching methods, guidance and reflection on the implementation of learning, evaluation and strengthening cultural literacy in learning. This study provides implications for applying a coaching model based on cultural literacy to improve the quality of early childhood education by strengthening local culture-based teaching. This requires ongoing teacher training, development of relevant curriculum, and evaluation and reflection to enhance the implementation of culture-based learning.